Motivational affective factors and literacy learning in students of the second grade of primary from School No. 64668 La Perla Yarinacocha, 2018 - Chávez Epiquén, Abdías Chávez Epiquén (2019)
The study was proposed to determine the relationship between motivational affect factors and literacy learning in children of the second grade of primary school. The research, by its nature, was theoretical; by its scope, descriptive, and by its purpose, quantitative; as a general method, it was used the scientific one, and in a specific way, the descriptive one, with a descriptive correlational design. For the sample, 70 second-grade primary school students were taken in a census way from Educational Institution No. 64668 La Perla from Yarinacocha, province of Coronel Portillo. The observation technique and its instrument, the observation guide, were used on the variables affective motivational factors and literacy learning. It was concluded that there is a direct relationship between these variables, with a Spearman’s rho coefficient of 0.609, at a 0.05 of significance. The better the affectivity develops, the more literacy will develop.   DOI: https://doi.org/10.31876/sl.v2i1.36